USAHA MEMPRODUKSI SABUN KOLAGEN DENGAN BAHAN KOLAGEN DARI SISIK IKAN BANDENG (Chanos chanos) DI BUDURAN-SIDOARJO - Suseno, Suseno; Listyaningrum, Niken Prawesti; Wilujeng, Arum Fristia (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
The milkfish processing process produces waste in the form of milkfish scales. In order to apply the Zero waste principle, milkfish scales can be used as collagen. Collagen is the main structural protein in the connective tissue of animal skin and bones. The production of collagen can be done through an extraction process and there are two ways of extraction that can be done, namely conventional extraction using solvents and enzymatic extraction using protease enzymes. The reason the author took the title business of producing collagen soap with collagen from milkfish scales (Chanos chanos) was to determine the level of consumer preference for collagen soap and the business costs of producing collagen soap. This research is an experimental study by giving treatment with different concentrations of collagen in 1%, 2% and 3% soap. The results showed that the difference in the concentration of collagen in collagen soap did not have a significant effect on organoleptic tests and consumer preferences. The highest value based on organoleptic tests and consumer preferences was found in the addition of 2% collagen.